Dinosaur Heresies: New Theories unlocking the Mystery of the Dinosaurs and Their Extinction - Robert T Bakker; BAKKER (Robert T) (New York William Morrrow & Co, 1986)
The inside story of a scientific heresy that is scandalizing traditional paleontology, told by the unorthodox leader of the dinosaurian heretics and featuring over 200 original black-and-white drawings that show how dinosaurs lived.
Keywords: Fossil Cold Blooded Vertebrates; Brontosaurus; Animal History